Anti-polyribosylribitol phosphate antibody concentrations and avidities in children since the start of Haemophilus influenzae type b immunization of infants in the United Kingdom. - Kelly, D; Moxon, E; Yu, L; Pollard, A (2009)
The introduction of routine infant immunization with Haemophilus influenzae type b (Hib) conjugate vaccines in the United Kingdom in 1992 led to a significant reduction in invasive disease due to this organism. Subsequently, between 1999 and 2003 there was an increase in the number of immunized children with Hib infection. We investigated whether the rise in cases was related to changes in anti-polyribosylribitol phosphate (PRP) antibody concentration or avidity. Using stored sera, we analyzed temporal changes in antibody levels among 3- to 5-year-old children immunized between 1991 and 2000. Anti-PRP antibody concentrations were higher in 3- to 5-year-olds who received infant immunization in 1991 than those in subsequent years. This difference may be related to changes in either the mode of administration of Hib conjugate vaccines or the rates of Hib nasopharyngeal carriage. This study emphasizes the factors affecting anti-PRP antibody concentration following immunization with conjugate vaccines and the importance of these in long-term protection from invasive disease.